Effects of exercise and bryostatin-1 on serotonin dynamics after cerebral infarction. Issue 9 (15th June 2016) - Mizutani, Kenmei; Sonoda, Shigeru; Wakita, Hideaki; Okazaki, Hideto; Katoh, Yoshimitsu; Chihara, Takeshi; Shimpo, Kan
Abstract : Although it has been suggested that the combination of exercise and bryostatin-1 administration may induce greater functional recovery than exercise alone, the detailed molecular mechanisms are not well known. Here, we examined the relationship between this combination treatment and monoamine dynamics in the cerebral cortex peri-infarction area to promote our understanding of these molecular mechanisms. Experimental cerebral cortex infarctions were produced by photothrombosis in rats. Voluntary exercise was initiated 2 days after surgery. Motor performance was then measured using the rotarod test. Monoamine concentrations in the perilesional cortex were analyzed by high-performance liquid chromatography. In behavioral evaluations, performance in the rotarod test was significantly increased by exercise. Moreover, performance in the rotarod test after the combination of exercise and bryostatin-1 administration was significantly greater than that after exercise alone. In the analysis of monoamines, serotonin (5-HT) concentrations were significantly higher in the groups treated with exercise and bryostatin-1. In addition, 5-HT turnover was significantly lower in the groups treated with exercise and bryostatin-1. Furthermore, the mean latency in the rotarod test showed a significant positive correlation with 5-HT levels. In immunohistochemical analysis, 5-HT immunoreactivity in the dorsal raphe nucleus was shown to be higher in the groups treated with exercise. In the present study, we detected changes in the levels of monoamines associated with the combined treatment of exercise and bryostatin-1 administration in the perilesional cortex. It has been suggested that this combination of therapies may affect 5-HT turnover and serve to increase local 5-HT concentrations in the perilesional area.